Thymic B cells of pig fetuses and germ-free pigs spontaneously produce IgM, IgG and IgA: detection by ELISPOT method - Cukrowska, B; Sinkora, J; Mandel, L; Splíchal, I; Bianchi, A T; Kovárů, F; Tlaskalová-Hogenová, H (Immunology, 1996)
The aim of this study was to investigate spontaneous immunoglobulin production and a pattern of isotype switching by thymic B lymphocytes (TBL) as compared with cells isolated from spleen during early ontogeny using a pig model in which B-cell development is not influenced by maternal regulatory factors. A sensitive ELISPOT assay was therefore employed to detect immunoglobulins in pig fetuses, colostrum-deprived germ-free (GF) piglets as well as conventionally (CONV) reared pigs. The first spontaneously immunoglobulin-secreting cells in the thymus were detected in 67-day-old fetuses (the length of gestation period in pigs is 114 days), their number increasing during fetal ontogeny. In contrast to fetal splenic cells, which secrete exclusively IgM, fetal thymic immunoglobulin-secreting cells were determined to undergo spontaneous isotype switching to IgG and IgA. In 28-day-old GF piglets and 3-month-old CONV pigs the number of thymic immunoglobulin-secreting cells of all isotypes was comparable to the number of thymic immunoglobulin-secreting cells detected in the newborn thymus. Considerable augmentation of IgG and IgA production by splenic immunoglobulin-secreting cells in CONV pigs was observed as compared to GF newborns and GF piglets, in which IgG- and IgA-secreting cells were detected occasionally. Our results indicate that TBL represent the first B-cell population in early fetal ontogeny spontaneously undergoing isotype switching to IgG and IgA; in the postnatal period the TBL population does not appear to be influenced by external antigenic stimuli of conventional microflora.
Keywords: Swine, Miniature; imunoglobulin G; Gestational Age; přesmyk imunoglobulinových tříd; Immunoglobulin M; gnotobiologické modely; miniaturní prasata; slezina; Immunoglobulin A; Immunoglobulin Isotypes; Immunoglobulin Class Switching; gestační stáří; imunoglobulin M; Swine; B-lymfocyty; Immunoglobulin G; ELISA; zvířata; B-Lymphocytes; Germ-Free Life; imunoglobulin A; Thymus Gland; imunoglobulinové izotypy; prasata; Enzyme-Linked Immunosorbent Assay; thymus; Spleen; Animals